Design, Simulation and Comparison of Control Strategies for the Optimal Positioning of Mobile Wireless Sensor Networks - Urrea-Onate, E; Adasme-Soto, P (Institute of Electrical and Electronics Engineers Inc., 2022)
With the development of the Wireless Sensor Network, positioning has taken on a relevant role, either because of the low costs of the technology or because of the ease of implementation. As far as we know, the application of positioning control strategies has not been deeply developed. The present investigation compares three control strategies applied in the positioning of a sensor node, using spherical trilateration. First, the analysis scenario was established, the PD controller was used as a comparative base and then a Fuzzy PD controller, Kalman Filter, and a Neural Network were applied. All controllers were analyzed with the same input data and 200 iterations. The main results analyzed were the errors of the antennas, the distance between the reference point and the estimated one, together with the position in the X and Y axis, being the Kalman filter the one that presented the best performance in the established base scenario. © 2022 IEEE.